Kepatuhan Lembaga Amil Zakat Sebagai Bentuk Pertanggungjawaban Keuangan Dari Aspek Akuntansi - Ahmad Kudhori; Hedi Pandowo (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
Abstract— This study aims to determine the compliance of amil zakat institutions in financial management (accountability) in terms of the background of the financial manager. The research method uses descriptive qualitative analysis with a multiple case study model of national amil zakat institutions that have zakat distribution in Madiun Raya and are members of the Madiun Raya Regional Zakat Organization Forum (FOZDA), namely BAZNAS, LMI, LAZISMU, Yatim Mandiri, BMH, Global Zakat, Nurul Hayat and Dompet Duafa. Collecting data using in-depth interviews, observation and documentation to informants at each institution. The results of this study indicate that the understanding of accounting, financial reports and applicable standards of the financial staff of the amil zakat institution is different, which is due to the educational background, years of service and position of the institution in Madiun, whether as a branch office, unit or outlet. However, office governance, finance, management and human resources within the institution can work together, so that the compliance of the amil zakat institution in carrying out accounting (accounting) which produces output in the form of financial reports can run well, as a form of transparency and accountability to donors. Keywords—: Amil Zakat Institution; Accounting; Financial statements; PSAK 109.